Cervical vertebral body replacement using a modern in situ expandable and angulable corpectomy cage system: early clinical and radiological outcome - Darwich, Ali; Vogel, Johannes; Dally, Franz; Hetjens, Svetlana; Gravius, Sascha; Faymonville, Christoph; Bludau, Frederic (British journal of neurosurgery, 2023)
Vertebral body replacement (VBR) cages are commonly implanted to reconstruct the cervical vertebrae in cases of tumour, trauma, spondylodiscitis, and degeneration. Expandable cages have been widely used for this purpose; however, the lacking congruence at the implant-bone interface and consequent implant displacement were considered as a serious drawback of such systems. Aim of this study is to evaluate the early clinical and radiological outcome of a modern in situ not only expandable but also angulable cervical corpectomy cage system. A total of 42 patients who underwent a single or multilevel cervical VBR procedure were included and retrospectively evaluated in this single-centre case series. The neurological status was assessed using American Spinal Injury Association (ASIA) score. Complications were categorized into surgical (including implant-associated) and general medical. Radiographic parameters included regional angulation, segmental height, and coronal alignment. Mean age was 59.5 ± 20.6 years. The recorded ASIA score improved postoperatively by 10 points (p 0.0001). Surgical including implant-associated complication rates were 19.05%. Radiographic evaluation showed a height gain of 11.2 mm (p < 0.0001), lordotic correction of 7° (p < 0.0001), and coronal alignment of 3° (p < 0.0001). At the last follow-up, loss of angulation correction of 1.9° (p 0.0002), subsidence of 1.92 mm (p 0.0006), and fusion rates of 68.42% were observed. The use of an in situ angulable and expandable cage system in cervical VBR seems to offer better results compared to conventional static or expandable cages regarding segmental height gain, lordotic correction, and clinical improvement as well as low complication and revision rates. Significant height gain in multilevel surgeries is associated with higher rates of implant-associated complications.